2023
DOI: 10.3390/vaccines11030582
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the Self-Reported Likelihood of Receiving the COVID-19 Vaccine, Likelihood of Contracting COVID-19, Discrimination, and Anxiety/Depression by Sexual Orientation

Abstract: There is limited evolving literature on COVID-19 vaccine uptake and its barriers among sexual minority populations (lesbian, gay, bisexual, transgender, and queer [LGBTQ]), despite their increased COVID-19 risk factors. We assessed the differences in intention to receive the COVID-19 vaccine by self-reported likelihood of contracting COVID-19, anxiety/depression, discrimination frequency, social distancing stress, and sociodemographic factors across sexual orientation. An online national cross-sectional survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
4
1
Order By: Relevance
“…This study discovered that depressive symptoms at baseline did not significantly predict MoVAC-19 4 years later. However, this finding is not consistent with those of a previous cross-sectional study [ 15 ]. The present study assessed the participants’ self-reported depressive symptoms within the preceding month at baseline.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This study discovered that depressive symptoms at baseline did not significantly predict MoVAC-19 4 years later. However, this finding is not consistent with those of a previous cross-sectional study [ 15 ]. The present study assessed the participants’ self-reported depressive symptoms within the preceding month at baseline.…”
Section: Discussioncontrasting
confidence: 99%
“…The National Immunization Survey Adult COVID Module, United States between 29 August and 30 October 2021 demonstrated that 8.2% of gay or lesbian individuals and 10.2% of bisexual individuals reported that they probably or definitely would not get vaccinated [ 14 ]. In addition, a study in the United States between 13 May 2021 and 9 January 2022 demonstrated that sexual minority individuals had a lower intention of receiving the COVID-19 vaccine (65.62%) than heterosexual individuals (67.56%) [ 15 ], whereas a study in Taiwan between 15 October 2020 and 21 December 2020 found that LGB individuals had a higher level of intention to get vaccinated against COVID-19 compared with heterosexual individuals [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The associations between receiving information on mpox from social media and from health-care providers and mpox-vaccine uptake need to be studied further. Second, a study revealed that lesbian, gay, bisexual, transgender, and queer individuals with severe or moderate depression and anxiety were less likely to receive COVID-19 vaccination [ 26 ]. According to PMT, emotional problems may reduce the self-efficacy of individuals in adopting coping strategies and overcoming the difficulty of receiving vaccination [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%